Anti-titin antibody is associated with more frequent hospitalization to manage thymoma-associated myasthenia gravis - Kim, Ki Hoon; Kim, Seung Woo; Cho, Jinhyuk; Chung, Hye Yoon; Shin, Ha Young (Frontiers in Neurology, 2022)
Background and Purpose: Anti-titin antibodies are anti-striational antibodies associated with thymoma-associated myasthenia gravis (MG). We evaluated whether the patients with anti-titin antibody are more frequently hospitalized to manage thymoma-associated MG than those without. Methods: Patients with thymoma-associated MG who conducted the serologic test for anti-titin antibody were retrospectively included. Disease severity, treatments, MG-related annual hospitalization rate, and MG-related emergency room (ER) visit rate was compared between the patients with anti-titin antibody and those without. Multivariate analysis was conducted to analyze the association between anti-titin antibody serostatus and multiple admission (hospitalization or ER visit of ≥2 times). Results: Of the 64 included patients, 31 (48.4%) patients were positive for anti-titin antibody (titin + group) and 33 (51.6%) were negative (titin – group). Both annual rate of MG-related hospitalization and ER visit were significantly higher in the titin + group (0.2 [0.1–0.6] and 0.1 [0–0.2] per year, respectively) than those in the titin – group (0 [0–0.2] and 0 [0–0] per year, p=0.004 and p=0.006, respectively). In multivariate analysis, positive anti-titin antibody was still significantly associated with multiple admission (OR 4.11, 95% CI 1.05–16.03) compared to titin – group as reference after adjusting for sex, follow-up duration, age at onset, systemic chemotherapy, and Masaoka staging. Conclusions: Presence of anti-titin antibody is associated with more frequent hospital utilization. Personalized explanation and careful monitoring strategy could be required in patients thymoma-associated MG with anti-titin antibody for the timely detection of relapses.